Inequality, poverty and child benefits: Evidence from a natural experiment - Piotr R. Paradowski; Joanna Wolszczak-Derlacz; Eva Sierminska (Luxembourg Income Study (LIS), 2020)
We assess the impact of a new policy action in the form of cash child benefit introduced in Poland in 2016 (the program Family 500 +) on inequality and poverty. The analysis is based on micro-level household data from the Luxembourg Income Study (LIS) and Statistics Poland. We examine the changes in various indicators of inequality and poverty (Gini index, subjective and relative poverty rates) and their decomposition. We find evidence that the program substantially reduces inequality and poverty. This is confirmed by difference-in-difference estimation, in which treated and non-treated households are compared before and after the program's introduction.
Keywords: I32; I38; G15; 330; inequality; poverty; child benefit